CLSM-guided imaging provides new insights into position-dependent limitations of endodontic disinfection - Sarah Böcher; Rebecca Mattern; Georg Conrads; Andreas Braun; Johannes-Simon Wenzler (Clinical Oral Investigations, 2026)
Abstract Objectives Insufficient bacterial reduction remains a major cause of endodontic treatment failure. Adequate disinfection is challenging, due to microbial migration into the tubules of the surrounding root dentin. This study aimed to further develop a novel confocal laser scanning microscopy (CLSM) model using LIVE/DEAD staining to provide new insights into endodontic disinfection. Materials and methods Thirty human teeth were inoculated with Enterococcus faecalis using a previously established protocol (A-Pr2). The area of bacterial colonization and bacterial eradication and the presence of residual bacteria within the irrigated area were evaluated using CLSM-guided imaging with LIVE/DEAD staining, and the sclerosis grade (SCG) of each sample was assessed. The effects of disinfection measures (conventional irrigation plus/minus sonic-activation), position (coronal, medial, apical), and sclerosis grade were analyzed. Results Root canal position showed a statistically significant ( p < 0.05) main effect on bacterial colonization and bacterial eradication, while neither treatment nor sclerosis grade showed statistically significant ( p > 0.05) main effects. Although the area of bacterial eradication descriptively decreased with increasing sclerosis grade, this trend did not reach statistical significance. Residual bacteria within the irrigated area were more likely in medial and apical than in coronal regions (OR 2.67 and 2.74; both unadjusted p < 0.05), with adjusted probabilities of 45.5% (coronal), 69.0% (medial), and 69.6% (apical). Conclusions Position within the root canal emerged as the primary determinant of bacterial colonization, extent of bacterial eradication, and risk for persistence of residual bacteria within the irrigated area, highlighting the predominant influence of anatomical location over the investigated treatment variables. Clinical relevance Future endodontic disinfection strategies should address position-dependent limitations and aim to reduce the overall bacterial load by considering both the spatial extent (disinfection quantity) and intensity (disinfection quality) of bacterial eradication, rather than penetration depth alone.